2018
DOI: 10.1002/hyp.11468
|View full text |Cite
|
Sign up to set email alerts
|

Importance of river water recharge to the San Joaquin Valley groundwater system

Abstract: Groundwater is not a sustainable resource, unless abstraction is balanced by recharge. Identifying the sources of recharge in a groundwater basin is critical for sustainable groundwater management. We studied the importance of river water recharge to groundwater in the south‐eastern San Joaquin Valley (24,000 km2, population 4 million). We combined dissolved noble gas concentrations, stable isotopes, tritium, and carbon‐14 analyses to analyse the sources, mechanisms, and timescales of groundwater recharge. Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 72 publications
(135 reference statements)
7
29
1
Order By: Relevance
“…In fact, all winter uplift features on the eastern side of the valley (e.g., P w 2, P w 4, and P w 6) are associated with lower δ 18 O concentrations. While we do not observe a similar, distinct winter uplift feature along the Kings River, the region of lowest δ 18 O content in the Visser et al (2018) study, this could be due to the perennial nature of the Kings (i.e., recharge occurring with more regularity rather than just seasonally) and that the coarser-grain material underlying the region is less susceptible to high-amplitude deformation related to changes in pore pressure. The agreement between these two independent data sets underscores the potential utility of these new observations of uplift timing and evolution as a tool for understanding groundwater recharge and flow.…”
Section: Implications For Groundwater Recharge and Flow Within The Sjvcontrasting
confidence: 78%
See 1 more Smart Citation
“…In fact, all winter uplift features on the eastern side of the valley (e.g., P w 2, P w 4, and P w 6) are associated with lower δ 18 O concentrations. While we do not observe a similar, distinct winter uplift feature along the Kings River, the region of lowest δ 18 O content in the Visser et al (2018) study, this could be due to the perennial nature of the Kings (i.e., recharge occurring with more regularity rather than just seasonally) and that the coarser-grain material underlying the region is less susceptible to high-amplitude deformation related to changes in pore pressure. The agreement between these two independent data sets underscores the potential utility of these new observations of uplift timing and evolution as a tool for understanding groundwater recharge and flow.…”
Section: Implications For Groundwater Recharge and Flow Within The Sjvcontrasting
confidence: 78%
“…Water with a relatively lighter isotopic signature (depleted in the heavier isotopes) is then channeled and transported into the SJV by Sierra-sourced rivers. Visser et al (2018) found plumes of depleted δ 18 O concentrations in groundwater samples originating near the Kings, Kaweah, Tule, and Kern Rivers (their Figure 4b), emphasizing the role that these rivers play in the recharge of the aquifer system. In fact, all winter uplift features on the eastern side of the valley (e.g., P w 2, P w 4, and P w 6) are associated with lower δ 18 O concentrations.…”
Section: Implications For Groundwater Recharge and Flow Within The Sjvmentioning
confidence: 95%
“…In our simulations, the majority of this recharge comes from the MFR pathway, the ratio of MFR/(MBR + MFR) ranges from 0.85 to 0.99 across all simulations performed. Our results are consistent with observational studies (Visser et al, 2018), but there is considerable uncertainty related to characterizing the source of mountain system recharge. The simulated MFR depends on the subsurface permeability values assigned to the Central Valley aquifer in the piedmont slope region.…”
Section: Recharge Pathway Sensitivity To Meteorological Variabilitysupporting
confidence: 91%
“…Still other works have identified river waters that have been diverted for irrigation as important recharge sources (e.g., Bajjali, ). In California's Central Valley, river‐borne recharge has been identified in well waters with large proportions of recent recharge, signifying irrigation practices generate recharge (Visser et al, ; see also Criss & Davisson, ). In other aquifer systems underlying heavily irrigated lands, isotopic data show that irrigation return flows more likely derive from intensive groundwater‐fed irrigation than from diverted river waters (e.g., North China Plain—von Rohden et al, ; Sbeïtla Aquifer in Tunisia—Dassi, ; and portions of California's Central Valley—Davisson & Criss, ).…”
Section: Recharge Sources and Elevationsmentioning
confidence: 99%